ANALISIS EFEKTIVITAS, AKUNTABILITAS, TRANSPARANSI PENGELOLAAN DANA BOS TERHADAP PENGADAAN SARANA DAN PRASARANA SEKOLAH (Studi Kasus Sekolah SMK NEGERI 6 Sukoharjo) - Novita Sari; Desy Nur Pratiwi; Sri Laksmi Pradanawati (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This study aims to examine the effect of effectiveness, accountability, and transparency of the management of School Operational Assistance Funds (BOS) on the successful procurement of school facilities and infrastructure. The object of this research is all students of class XI of SMKN 6 Sukoharjo who use facilities and infrastructure at school. This study uses primary data obtained through the distribution of questionnaires. The sampling technique used the Slovin formula from the total population of grade XI students, with an error rate of 5%, so that 179 respondents were obtained. Data analysis techniques used in this study include descriptive statistics, validity and reliability tests, classical assumption tests, and multiple linear regression tests. The results showed that the effectiveness of BOS Fund management had no significant effect on the successful procurement of facilities and infrastructure, with a significance value of 0.318 > 0.05 and tcount 1.001 < 1.973. Accountability has a positive and significant effect on the successful procurement of facilities and infrastructure, with a significance value of 0.000 < 0.05 and tcount 4.418 > 1.973. Transparency also has a positive and significant effect on the successful procurement of facilities and infrastructure, with a significance value of 0.001 < 0.05 and tcount 3.295 > 1.973.